The Impact Of Integrated Psychospiritual Module Among The Drug Addicts In Malaysia In Elevating The Psychospiritual And Drug-related Locus Of Control Level Towards The Decrease Of Relapse Rate. - Amin Al Haadi Bin Shafie; Nurul Ashikin Binti Ahmat Miskam; Fatini Athilah Binti Elias; Mohd Rushdan Mohd Jailani; Hishamuddin Abdul Wahab (Human Resource Management Academic Research Societ, 2024)
Indexed by ERA